Valorization of Rice Husk (Oryza sativa L.) as a Source of In Vitro Antiglycative and Antioxidant Agents - Ilaria Frosi; Daniela Vallelonga; Raffaella Colombo; Chiara Milanese; Adele Papetti (Foods, 2023)
Rice husk is a good source of polyphenols, but it has not been efficiently utilized in food applications yet. Therefore, the aim of this work is to investigate, by in vitro assays, the polyphenolic extract (RHE) capacity of this waste to counteract the protein glycation at different stages of the reaction, correlating this activity with the antiradical properties. A microwave-assisted extraction using hydro-alcoholic solvents was applied to recover husk polyphenols. Extraction parameters were optimized by the design of the experiment. The extract with the highest polyphenolic recovery was obtained at 500 W and 90 °C, using 1:35 g of dry material/mL solvent, 80% ethanol, and a 5 min extraction time. Results highlight the ability of RHE to inhibit the formation of fructosamine in the early stage of glycation with a dose-dependent activity. Furthermore, in the middle stage of the reaction, the highest RHE tested concentration (2.5 mg/mL) almost completely inhibit the monitored advanced glycation end products (AGEs), as well as showing a good trapping ability against α-dicarbonyl intermediates. A strong positive correlation with antioxidant activity is also found. The obtained results are supported by the presence of ten polyphenols detected by RP-HPLC-DAD-ESI-MSn, mainly hydroxycinnamic acids and flavonoids, already reported in the literature as antiglycative and antioxidant agents.